Nelayan dan Kemiskinan : Studi Kualitatif Strategi Nelayan Desa Teluk Setimbul Dalam Memenuhi Kebutuhan Hidup Keluarga - Sujarwo Sujarwo (Universitas Muhammadiyah Sumatera Utara, 2022)
The amount of income earned by fishermen in Teluk Setimbul village is very worrying, the fishermen in Teluk Setimbul village do not have a steady income. The income of fishermen is very dependent on the catch of fish, if fishermen do not succeed in getting fish, they will not get income to meet the needs of their families. This study aims to obtain a clear and in-depth picture of the survival strategies carried out by fishermen in meeting the needs of family life. This research was conducted using a qualitative approach, which attempted to describe the efforts of the fishing community in overcoming poverty through the case study method. Data collection techniques were carried out by interview, observation, and documentation study. The results of the study show several strategies carried out by fishermen, including; make loans to relatives or neighbors, do a double life pattern, and do side jobs to increase family income.Keywords: Fishermen, Poverty, Subsistence Strategies.